FDI in the banking sector - Beatriz de Blas; Katheryn Russ (University of California, Department of Economics, 2010)
It is a well known quandry that when countries open their financial sectors, foreign-owned banks appear to bring superior efficiency to their host markets but also charge higher markups on borrowed funds than their domestically owned rivals, with unknown impacts on interest rates and welfare. Using heterogeneous, imperfectly competitive lenders, the model illustrates that FDI can cause markups (the net interest margins commonly used to proxy lending-to-deposit rate spreads) to increase at the same time efficiency gains and local competition keep the interest rates that banks charge borrowers from rising. Competition from arms-length foreign loans, however, both squeezes markups and lowers interest rates. We show that allowing foreign participation is not always a welfare-improving substitute for increasing competition and technical efficiency among domestic banks.
Keywords: 330